2023
DOI: 10.1177/03635465221150507
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport After Nonoperative Management of Elbow Ulnar Collateral Ligament Injuries: A Systematic Review and Meta-analysis

Abstract: Background: Elbow ulnar collateral ligament (UCL) injuries can result in significant functional impairment in throwing and overhead athletes. UCL reconstruction and repair are proven treatments to restore stability, but the efficacy of nonoperative management is unclear. Purpose: To determine the rate of return to sports (RTS) and return to previous level of play (RTLP) in athletes sustaining medial elbow ulnar collateral ligament (UCL) injuries treated nonoperatively. Study Design: Systematic review; Level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
(113 reference statements)
0
0
0
Order By: Relevance
“…Distal tears have been found to be significantly more likely to fail nonoperative management and have a poorer prognosis when compared with proximal tears, potentially due to decreased vascularity around the distal segment of the ligament. 6,15,16,38 Given this association, it is possible that the mechanism of injury may have a prognostic role in these patients. Further studies with larger sample sizes are needed to validate these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Distal tears have been found to be significantly more likely to fail nonoperative management and have a poorer prognosis when compared with proximal tears, potentially due to decreased vascularity around the distal segment of the ligament. 6,15,16,38 Given this association, it is possible that the mechanism of injury may have a prognostic role in these patients. Further studies with larger sample sizes are needed to validate these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Although nonoperative management of partial MUCL tears can result in a quicker RTP, treatment outcomes can be less predictable, especially among professional throwers, in whom RTP has been reported to be as low as 46% to 57%. 7,23 In contrast, UCLR can provide more reliable outcomes, with many studies suggesting RTP rates from 80% to 97%. 3,42 For high-level athletes, consideration must be given not only to initial cost of treatment, but also to longevity of their careers after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have evaluated biologic supplementation and its role in injury management. 7,12,23,37 In a case study of 34 amateur athletes with partial-thickness UCL tears who underwent PRP injections, Podesta et al 37 found at a mean follow-up of 70 weeks that 88% had returned to the same level of play with an 8-mm decrease in medial joint space opening with valgus stress as measured by ultrasound. In a similar study, Deal et al 12 found reconstitution of the MUCL via MRI after PRP injections in 23 of 25 amateur throwers after their RTP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations